How orthodontics can facilitate restorative dentistry - CHALALA, Chimène (International Arab Journal of Dentistry (IAJD), 2012)
Full comprehensive orthodontic treatment is often a requisite in the rehabilitation of oral form and function specifically when anterior restoration(s) is (are) needed. Patients with missing, abraded or fractured teeth, peg-shaped lateral incisors, or other restorative needs may require tooth movement for optimal treatment outcomes. Such treatment necessitate collaboration between the orthodontist and others specialties, such as the restorative dentist and / or the periodontist. The major indication for adjunctive orthodontic treatment is to facilitate and improve the dental restorative conditions at the level of the arch (space management), roots (parallel abutments) and bone height (periodontal considerations) for the placement of well-adapted and contoured restorations, crowns or implants. This interdisciplinary management will be illustrated through specific dental treatment phases, in addition to the assessment of guidelines for general dentists, specialists, and orthodontists to establish a comprehensive treatment plan and execute it in an orderly way toward successful results.